Effect of transcranial direct current stimulation combined with cognitive rehabilitation on cognitive function and activities of daily living in patients with post-stroke cognitive impairment: a systematic review and meta-analysis - Luo, Nan; Zhao, Binbin; Wang, Hui; Wu, Jiabei; Luo, Yifan; Yuan, Man; Xu, Chunlan (Frontiers in Neurology, 2025)
ObjectiveThe incidence of post-stroke cognitive impairment (PSCI) has increased alongside the rising prevalence of stroke, making it one of the most serious and prevalent complications among stroke survivors. Growing interest has emerged in whether combined or multi-modal therapies can enhance outcomes through additive or synergistic effects, leading more researchers to investigate the efficacy of transcranial direct current stimulation (tDCS) combined with cognitive rehabilitation (CR) in this population. This study aims to systematically review and meta-analyze the effects of tDCS combined with CR on cognitive function and activities of daily living (ADL) in individuals with PSCI.MethodsPubMed, Web of Science, Cochrane Library, Embase and China National Knowledge Infrastructure (CNKI) were systematically searched for articles published from inception of the databases through June 2024. Two independent authors screened studies and extracted data. The methodological quality of the included randomized controlled trials (RCTs) was evaluated with the Cochrane Risk of Bias Tool. Meta-analyses were performed using R statistical software (version 4.1.2).ResultsA total of 663 participants across 11 RCTs published between 2013 and 2024 were included. The meta-analysis results indicated that tDCS combined with CR significantly improved cognitive function and ADL among PSCI patients compared to the control group, as evidenced by the Montreal Cognitive Assessment test (MoCA) (MD = 3.03, 95% confidence interval = 2.07 ~ 3.99, p < 0.0001), Mini-Mental State Examination (MMSE) (MD = 1.73, 95% confidence interval = −0.05 ~ 3.52, p < 0.05), Loewenstein Occupational Therapy Cognitive Assessment (LOTCA) (MD = 11.98, 95% confidence interval = 10.02 ~ 13.93, p < 0.0001), Activity of Daily Living Scale (ADLs) (MD = 2.54, 95% confidence interval = 0.76 ~ 4.31, p < 0.05), and Modified Barthel Index (MBI) (MD = 5.23, 95% confidence interval = 1.82 ~ 8.64, p < 0.01). Subgroup analysis results revealed that tDCS combined with computer-assisted cognitive rehabilitation (CACR) had a greater positive impact on ADL.ConclusiontDCS combined with CR significantly improves cognitive function and ADL among individuals with PSCI. Compared with conventional cognitive rehabilitation, the computer-assisted approach demonstrates greater effectiveness in improving ADL among PSCI patients.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier [CRD42024561767].